1984
DOI: 10.1002/ajmg.1320190321
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal recessive disorder with glomerular basement membrane abnormalities similar to those seen in the nail patella syndrome: Report of a kindred

Abstract: We present a 9-year-old boy, the product of a consanguineous marriage, with proteinuria, edema, and microscopic hematuria with mild renal impairment since age 2 yr. Renal biopsy showed the histopathologic electron microscopic changes seen in hereditary osteo-onchyodysplasia (HOOD) [Hoyer et al, 1972; Bennet et al, 1973; DelPozo and Lapp 1970; Vernier et al, 1974; Morita et al, 1973] or "nail-patella syndrome." Neither the patient nor his relatives had bone or nail abnormalities; however, 2 other sibs had died … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Clinically acute, progressive disease manifested by protenuria and young age at onset might be comparable to the human childhood type of CFGN. Childhood CFGN is suspected to be an autosomal recessive disorder [7,15]; however, we were unable to investigate family history to ascertain whether this was implied in the present case. Except for family history, clinical and histopathological findings of the present dog were similar to CFGN-like glomerulosclerosis in three Newfoundland dog littermates [10].…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Clinically acute, progressive disease manifested by protenuria and young age at onset might be comparable to the human childhood type of CFGN. Childhood CFGN is suspected to be an autosomal recessive disorder [7,15]; however, we were unable to investigate family history to ascertain whether this was implied in the present case. Except for family history, clinical and histopathological findings of the present dog were similar to CFGN-like glomerulosclerosis in three Newfoundland dog littermates [10].…”
mentioning
confidence: 80%
“…As the majority of reported adult patients have been in Japan, geographic or racial predisposition may be assumed. The other, more severe type begins during childhood and an etiology of autosomal recessive transmission has been suggested [7,15]. Most patients exhibit progressive protenuria, eventually leading to nephrotic syndrome.…”
mentioning
confidence: 99%
“…As far as we know, a total of 29 cases have been reported (15 cases in Japan), suggesting a geographical or racial preponderance. The initial accumulation of reports suggested that this disease was adult-onset; however, Salcebo [24] reported a case involving a child in 1984. Recently, Gubler et al [22] have reported 10 cases in children and distinguished these from adult cases in regard to the clinical manifestations and family history.…”
Section: Discussionmentioning
confidence: 99%
“…14,18-20 They consist of focal or diffuse irregular thickening of the GBM containing patchy electron-lucent areas 18 and irregular deposition of type III collagen fibrils, especially in the lamina densa. 16,21 Few cases of nail-patella-like nephropathy with ultrastructural changes of the GBM similar to lesions observed in NPS and without nail and osseous anomalies have been published, [22][23][24] but the molecular bases of this phenotype have not been elucidated. Here, exome sequencing revealed a mutation in LMX1B segregating with disease in 3 of 74 families with isolated primary FSGS but no other known features of NPS.…”
mentioning
confidence: 99%